2008
DOI: 10.1299/jsdd.2.299
|View full text |Cite
|
Sign up to set email alerts
|

Hamiltonian Formulation of Surface and Interface Sloshing in a Tank Containing Two Immiscible Fluids

Abstract: This paper deals with surface and interface sloshing in a tank containing two fluids of different desities. Scientific interest in this ploblem includes the need to quantify allowance loads on oil water separators and chemical plants. In this study, we give a Hamiltonian formulation of a system of two incompressible irrotational fluids with a dynamic free surface and interface. This study aims to analyze the linearized time history response and the linear properties (vibration mode and effect of surface tensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 2 publications
0
12
0
Order By: Relevance
“…In the previous study, we reported that this system has two coupled resonance modes which have the same wave number (4) . The larger one is the dominant frequency of the surface…”
Section: N-wave Resonant Interaction (Nwri)mentioning
confidence: 95%
See 2 more Smart Citations
“…In the previous study, we reported that this system has two coupled resonance modes which have the same wave number (4) . The larger one is the dominant frequency of the surface…”
Section: N-wave Resonant Interaction (Nwri)mentioning
confidence: 95%
“…2, No.6, 2008 In the previous studies, we proposed the Hamiltonian formulation for this problem based on a variational principle (4) . Moreover, the experimental and the theoretical analyses are conducted to obtain the effect of surface tension on the natural frequencies (4) and the nonlinear time history responses (5) for this system. However, we couldn't discuss the nonlinear characteristics of surface and interfacial motions in detail.…”
Section: Journal Of System Design and Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…(1) - (4). Handa and Tajima (1) studied dispersion relations and amplitude-frequency responses of a two-dimensional model.…”
Section: Introductionmentioning
confidence: 99%
“…In the previous study, we gave canonical conjugate variables and Hamiltonian equations for this problem by a variational formulation (4) . Then, the experimental and theoretical analyses are conducted to investigate the effect of surface tension on the natural frequencies and the linearized problems for this system (vibration modes and time histories).…”
Section: Introductionmentioning
confidence: 99%